IKROM OTAMURODNING YOLG„IZLIK FALSAFASIGA YONDAShUVIDA RUHIYAT TALQINLARI - Jumaeva, S.Ch. (SCIENCE and SOCIETY, 2025)
This article will talk about spiritual interpretations of the philosophy of loneliness in the Zamiri of Ikrom Otamurod poetry. The author analyzed the philosophical observations expressed in the lyrics of Ikrom Otamurod and the poet's views on the interpretation of the psyche.
Keywords: poet; thoughtful thinking; loneliness; ideological-philosophical intention; in philosophical observation; artistic-aesthetic influence; spiritual-educational aspect